2015
DOI: 10.1175/jcli-d-14-00569.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent Intensification of the Western Pacific Subtropical High Associated with the East Asian Summer Monsoon

Abstract: The summer western Pacific subtropical high (WPSH) has intensified during the past three decades. However, the underlying mechanism is not yet well understood. Here, it is shown that baiu rainband activity in midsummer, which is part of the East Asian summer monsoon, plays an important role in recent intensification in the WPSH along the baiu rainband. In contrast with the WPSH, the summer Okhotsk high, which is located to the north of the baiu rainband, has weakened during the past three decades. The north–so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 33 publications
3
43
0
Order By: Relevance
“…The results indicate that diabatic heating plays a reinforcing role in the westward and intensified WNPSH, which are consistent with some previous studies (Zhou et al 2009;Matsumura et al 2015). However, some studies have found the WNPSH bias is also related to other bias in BCC_AGCM2.2, such as the wet bias over the Indian summer monsoon region, weak walker circulation, and lower air temperature over the Tibetan Plateau Kan et al 2015).…”
Section: Summary and Discussionsupporting
confidence: 91%
“…The results indicate that diabatic heating plays a reinforcing role in the westward and intensified WNPSH, which are consistent with some previous studies (Zhou et al 2009;Matsumura et al 2015). However, some studies have found the WNPSH bias is also related to other bias in BCC_AGCM2.2, such as the wet bias over the Indian summer monsoon region, weak walker circulation, and lower air temperature over the Tibetan Plateau Kan et al 2015).…”
Section: Summary and Discussionsupporting
confidence: 91%
“…We used realistic long-term experimental results (CTRL and NOMP runs) from Matsumura et al (2015a), which were obtained using cumulus parameterization (Grell and Dévényi 2002) and cloud microphysics (Hong et al 2004) for the cloud scheme. The model domain focuses on the NW Pacific poleward of 308N with a horizontal resolution of 25 km (170 3 150 grid) and 40 vertical layers.…”
Section: B Model and Experimental Designmentioning
confidence: 99%
“…1) might not satisfactorily capture the midlatitude atmospheric response to oceanic forcing. Indeed, recent tripolar-like precipitation changes (Matsumura et al 2015a) are not seen in Fig. 1, and the baiu rainfall response to KOE SST forcing remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations